Perceptions of Victimhood and Entrepreneurial Tendencies - Maaravi, Yossi; Hameiri, Boaz; Gur, Tamar (Frontiers in Psychology, 2022)
There is a growing scientific interest around entrepreneurship. One central line of research examines how different personality traits and characteristics such as creativity or resilience are related to entrepreneurial intentions and behavior. In the current research, we add to this literature by focusing on trait victimhood, a trait that entrepreneurship research has overlooked and may be relevant to understanding entrepreneurial tendencies. In two studies in Israel among a sample of entrepreneurship students (Study 1) and a sample representing the general public (Study 2), we show that trait victimhood is negatively related to entrepreneurial personality (Study 1) and behavior (Study 2). Moreover, Study 2 suggests that a strong sense of self-efficacy may buffer against trait victimhood's adverse effects on behavioral entrepreneurship.